REVIEW OF EKANYUNENA PURVENA SUTRA OF RELIGIOUS BOOK VEDAS IN CONTEXT OF MODERN MATHEMATICAL OPERATIONS - Lal, Rohit Ranjan; Yadav, Dharmendra Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Religious books not only preach for spiritual and natural power made by the possible almighty, if exists, but also give us the knowledge about our day-to-day life related problems including mathematical arithmetical calculations. In this paper we have analysed one of the sixteen sutras of Vedic Mathematics, known as Ekanyunena Purvena Sutra. The Vedic Mathematics sutras were derived from the Hinduism religious book Vedas. This sutra has been applied in finding the multiplication of two numbers, in which one number, called multiplier in the paper, is made of digit 9’s only. Throughout the paper such number has been taken as multiplier. In the paper three cases of the multipliers have been discussed and each has been derived from the algebraic expressions of the multiplication of two numbers. Thereafter they have been extended for any two numbers of any arbitrary numbers of digits. Some limitation has been mentioned before concluding the paper. The paper ends with a brief discussion on the future scope of research in this field.